1998
DOI: 10.1101/gr.8.5.509
|View full text |Cite
|
Sign up to set email alerts
|

A Map of 75 Human Ribosomal Protein Genes

Abstract: We mapped 75 genes that collectively encode >90% of the proteins found in human ribosomes. Because localization of ribosomal protein genes (rp genes) is complicated by the existence of processed pseudogenes, multiple strategies were devised to identify PCR-detectable sequence-tagged sites (STSs) at introns. In some cases we exploited specific, pre-existing information about the intron/exon structure of a given human rp gene or its homolog in another vertebrate. When such information was unavailable, selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
106
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 70 publications
2
106
0
5
Order By: Relevance
“…[5][6][7] RPS15A has been shown to be upregulated in response to the Myc oncogenic transcription factor or transforming growth factor-b induction. 8,9 Recent studies have indicated that RPS15A is implicated in several human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] RPS15A has been shown to be upregulated in response to the Myc oncogenic transcription factor or transforming growth factor-b induction. 8,9 Recent studies have indicated that RPS15A is implicated in several human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, ribosome proteins are synthesized stoichiometrically, in coordination with rRNA, to provide equimolar supply of ribosomal component [20]. The 75 human ribosomal protein genes have been mapped in 1998 [21]. However, their specific functions are not known individually.…”
Section: Discussionmentioning
confidence: 99%
“…HRPS19 is mapped to chromosome 19 [26], which is known to have a high gene density, contains an unusually large number (equal to 12) of ribosomal protein genes. Each mammalian ribosomal protein typically is encoded by a single gene.…”
Section: Discussionmentioning
confidence: 99%
“…RPS11, also known as the ribosomal protein S11, is part of the 40S ribosomal subunit (Feo, Davies and Fried, 1992;Kenmochi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%